SENSITIVE ELECTROCHEMICAL APTASENSOR FOR THE RAPID DETECTION OF CARCINOEMBRYONIC ANTIGEN - Yunussova, Nigara (Nazarbayev University School of Sciences and Humanities, 2025)
The development of diagnostic tools for cancer detection heavily relies on cancer biomarkers. Carcinoembryonic antigen (CEA) is a glycoprotein with a molecular weight ranging from 180 to 200 kDa and is widely recognized as a key biomarker for various cancers, including colorectal, pancreatic, gastric, and breast cancers, highlighting the importance of early and accurate detection to improve clinical outcomes. In Kazakhstan and globally, colorectal cancer, also known as bowel cancer or colon cancer, is the third most common cause of cancer-related deaths. Consequently, there is a pressing need to create diagnostic tests. Conventional CEA detection methods are often labor-intensive and slow, delaying timely treatment. In this study, a sensitive and specific electrochemical impedance spectroscopy (EIS)-based aptasensor was presented utilizing single-stranded DNA (ssDNA) aptamers as recognition elements. Compared to antibodies, aptamers offer several advantages, including smaller size, higher chemical stability, easier synthesis and modification, and enhanced selectivity. Previously, CEA aptamer sequences were identified by Dr. Kanayeva’s research group. The binding capability of the selected ssDNA aptamers against CEA was assessed using ELONA and bioinformatics analysis was done for better understanding the structures of the selected and characterized aptamers and aptamer-CEA complex. The identified most sensitive aptamer sequence (6) against CEA was next modified at the 5′-end with a thiol (-SH) C6 linker, an 18-HEG spacer, and a 5-thymine tail to enable effective immobilization on an interdigitated gold electrode (IDE). The resulting sensor enabled rapid CEA detection within 30 minutes, achieving detection limits of 2.4 pg/ml in buffer and 3.8 pg/ml in human serum, with minimal cross-reactivity to non-target proteins. IDE surface characterization using Atomic Force Microscopy (AFM) revealed increased roughness with each modification step, supporting successful aptamer immobilization and target capture. Confocal microscopy was acquired to visualize the CEA localization in cells and finally, the developed aptasensor was tested in CEA-expressing cell lines, T-84 and HT-29. underlining its potential for rapid, label-free cancer diagnostics.
Keywords: cancer; biosensors; cea; aptamers; type of access: embargo